Minimal Risk Level Derivation for Cadmium: Acute and Intermediate Duration Exposures - Obaid Faroon; Sam Keith; Moiz Mumtaz; Patricia Ruiz (Journal of Experimental and Clinical Toxicology, 2017)
The Agency for Toxic Substances and Disease Registry (ATSDR) lists cadmium as one of its priority hazardous substances. The agency conducted a comprehensive literature review of cadmium and used the information to develop a toxicological profile that identified the full range of health effects associated with exposure to cadmium. It included an assessment that identified screening levels, termed health guidance values or minimal risk levels (MRLs), below which adverse health effects are not expected. In this paper, we describe how MRLs for cadmium are derived. For the acute inhalation MRL, the traditional no observed adverse effect level or lowest observed adverse effect level (NOAEL/LOAEL) approach is used; for the oral intermediate MRL, the benchmark dose (BMD) approach is used. MRLs were developed for the most sensitive route-specific end points, other than mortality and cancer that were sufficiently supported and justified by the data. These included an acute duration (1–14 day exposure) inhalation MRL of 0.03 µg Cd/m3 for alveolar histiocytic infiltration and focal inflammation in alveolar septa and an intermediate duration (15–365 day exposure) oral MRL of 0.5 µg Cd/kg/day for decreased bone mineral density
Keywords: Cadmium